Analysis of Broiler Chicken Demand Influencing Factors in Pematangsiantar City - Restu Hajiis; Armyn Hakim Daulay; Edhy Mirwandhono; Tri Hesti Wahyuni; Hamdan . (Universitas Sumatera Utara, 2018)
Broiler chickens is a type of chicken that are able to grow and develop quickly. In addition, broiler chicken is one of favourite source of meat. The purpose of this research was to determined the affecting factors of demand of the broiler chicken meat demand in the Pematangsiantar city. The study was conducted in April-June 2018 using primary data. The method used in accidental sampling is respondent interview with purposive technique that analyzed by Multiple Linear Regression using SPSS 22 application tool. The results showed that broiler chicken demand in Pematangsiantar city was influenced simultaneously by broiler price, age, family member, family income, egg price, appetite level, and education level with R² = 0,51. The price of broiler chicken meat, age and the number of family members had a significant effected on the 95% confidence level.